Объяснение:
по следствию из первого замечательного предела
lim (1-cosx)/(x^2/2)=1
x->0
4x^2 умножим и разделим на 2 и 16 получится
4*(16*(x²)/2)*2/16=4[(4x)²/2]/8=[(4x)²/2]/2
=lim (1-cos4x)/4x² =
=lim (1-cos4x)/[(4x)²/2]/2 =
=lim 2 (1-cos4x)/[(4x)²/2] = заменим 4x=y
= 2 lim (1-cosy)/(y^2/2)=2
y->0
Объяснение:
по следствию из первого замечательного предела
lim (1-cosx)/(x^2/2)=1
x->0
4x^2 умножим и разделим на 2 и 16 получится
4*(16*(x²)/2)*2/16=4[(4x)²/2]/8=[(4x)²/2]/2
=lim (1-cos4x)/4x² =
x->0
=lim (1-cos4x)/[(4x)²/2]/2 =
x->0
=lim 2 (1-cos4x)/[(4x)²/2] = заменим 4x=y
x->0
= 2 lim (1-cosy)/(y^2/2)=2
y->0